Medically unexplained dyspnea： psychophysiological characteristics and role of breathing therapy - 韩江娜 朱元钰 李舜伟 雒冬梅 胡征 VanDiestI DePeuterS VandeWoestijneKP VandenBergh0 (Chinese medical journal, 2004)
Background Medically unexplained dyspnea occurs commonly in medical settings and remains poorly understood. This study was conducted to investigate the psychophysiological characteristics of medically unexplained dyspnea and the efficacy of breathing retraining for these patients.Methods A group of patients with medically unexplained dyspnea were compared to patients with a variety of organic lung diseases and healthy subjects. In another group of patients, the influence of breathing therapy on complaints, anxiety, and breath-holding was evaluated for an average of 1.5years.Results Patients with medically unexplained dyspnea reported more intense dyspnea than patients with a variety of organic lung diseases. Additionally, they were anxious and presented a broad range of symptoms in daily life and under challenge, for instance voluntary hyperventilation. More than one third of them qualified for panic disorder. They had shorter breath-holding time at rest, less in crease inbreath-holding time and higher chances of showing a "paradoxical" decrease of breath-holding time after hyperventilation. A combination of PaO2, forced expiratory volume in one second ( FEV1 ), andanxiety measures distinguished them from organic dyspnea. Breathing retraining profoundly improved their symptoms and decreased the level of state and trait anxiety. Moreover, they better tolerated the voluntary hyperventilation and the symptoms induced were also markedly decreased after therapy. Breath-holding time was prolonged and PetCO2 in a representative group of patients increased.Conclusions Patients with medically unexplained dyspnea appear to have the feature of a "psychosomatic" patient: an anxious patient with a wide variety of symptoms of different organ systems that do not have an organic basis. They can be distinguished from organic dyspnea using a small set of physiological and psychological measures. Breathing retraining turns out to be an effective therapy for those "difficult to treat patients".